2012
DOI: 10.5009/gnl.2012.6.3.349
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Endoscopic Erosive Esophagitis in Solid Organ Transplant Recipients

Abstract: Background/AimsSolid organ transplant recipients frequently report gastrointestinal symptoms, especially heartburn or dyspepsia. However, the prevalence of endoscopic erosive esophagitis (EE) and associated risk factors after transplantation are unknown. The aim of this study was to determine whether there was a high incidence of endoscopic findings of EE in solid organ transplant recipients.MethodsThis retrospective case-control study included 256 of 3,152 solid organ transplant recipients who underwent seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…GERD develops when increased acidic gastric secretion refluxes into the esophagus [ 3 , 4 ]. Gastrointestinal (GI) symptoms are commonly experienced in solid organ transplant recipients and can effects any part of the GI tract [ 5 ]. After three years of renal transplant, about 23% of the patients have GERD, reflux esophagitis (RE) and dyspepsia in 20%, 5% and 6%, respectively [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GERD develops when increased acidic gastric secretion refluxes into the esophagus [ 3 , 4 ]. Gastrointestinal (GI) symptoms are commonly experienced in solid organ transplant recipients and can effects any part of the GI tract [ 5 ]. After three years of renal transplant, about 23% of the patients have GERD, reflux esophagitis (RE) and dyspepsia in 20%, 5% and 6%, respectively [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neri et al proposed that renal transplanted patients having GERD, dyspepsia or reflux esophagitis are at increased risk of graft failure and death [ 6 ]. Kim et al reported severe complications in around 10% resulting in graft loss and death [ 5 ]. The rationale of this study is to determine factors leading to dyspepsia in renal transplant recipients, as no local study have been done so far for evaluation of dyspepsia in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…4 These injuries tend to occur early, usually within the first three to twelve months of initiating MMF therapy. 6 The risk of gastroduodenal erosions was approximately 1.83 fold for MMF, with the highest risk of erosive lesions associated with MMF-tacrolimuscorticosteroid combination treatment. [6][7][8] While it is important to consider MMF as a possible cause of esophageal injury in a post-transplant patient, one must first consider other more common causes, including reflux esophagitis, pill esophagitis, infectious esophagitis (HSV, CMV, and candida), radiation esophagitis, and corrosive ingestion.…”
Section: Discussionmentioning
confidence: 98%
“…6 The risk of gastroduodenal erosions was approximately 1.83 fold for MMF, with the highest risk of erosive lesions associated with MMF-tacrolimuscorticosteroid combination treatment. [6][7][8] While it is important to consider MMF as a possible cause of esophageal injury in a post-transplant patient, one must first consider other more common causes, including reflux esophagitis, pill esophagitis, infectious esophagitis (HSV, CMV, and candida), radiation esophagitis, and corrosive ingestion. In the middle and lower GI tract, the differential diagnosis should also include inflammatory bowel disease, infections (bacterial, viral, and parasitic), microscopic colitis, malabsorption, post-transplant immunoproliferative disease, and ischemia.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation